Пьесы - Островский Александр Николаевич (Бриллиантовая коллекция, 2006)
Экземпляры: ЦБ (20220329) / Инвентарный номер: 62877 / Цена: 50.00 / Сис.шифр: Р1 / Авт.знак: О-77 / ГРНТИ: 17.82.20 / ББК: 84(2Рос=Рус)1